Visible-Light-Induced Photoredox Construction of Trifluoromethylated Quaternary All-Carbon Centers and Tertiary Alcohols via C(sp3)–Si Bond Cleavage - Ma, Dandan; Chang, Lingna; Cai, Yue; Bai, Dachang (Synthesis, 2024)
The construction of trifluoromethylated quaternary carbon centers and tertiary alcohols is realized by organo-photoredox catalysis. The process proceeds via visible-light-induced C(sp3)–Si bond cleavage for the generation of α-trifluoromethylated benzyl radicals, which are readily trapped by electron-deficient alkenes with excellent regioselectivity for the construction of trifluoromethylated quaternary all-carbon centers. The α-difluoromethyl counterparts are also suitable for this radical conjugate addition. Furthermore, the in situ oxidation of these α-trifluoromethylated radicals with O2 from air affords tertiary alcohols in high yields, which extends the Fleming–Tamao reaction to tertiary carbon systems.
Keywords: visible-light-induced; trifluoromethylated quaternary carbon centers; tertiary alcohols; C(sp3)–Si bond cleavage; transition-metal-free